Warisan Budaya Cirebon: Mengungkap Sejarah dan Motif Batik Trusmi - Alfiannurdin, Nurlaila; Tresna, Pipin; Ruhidawati, Cucu (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This article uses a literature study approach to explore in depth the history and motifs attached to Trusmi batik, one of the unique cultural heritages of Cirebon. Using a literature study method, this research details the evolution of Trusmi batik making techniques as well as identifying and analyzing the meaning behind its distinctive motifs. The research results illustrate how this textile art reflects the traditional values and rich culture of Cirebon. The implications of these findings not only provide in-depth insight into Trusmi batik art but also provide a strong basis for efforts to preserve and develop local culture. This article has value as a guide for researchers, artists, and cultural observers who are interested in preserving cultural riches through traditional art, especially in the context of Trusmi batik in Cirebon. We can better appreciate and preserve the uniqueness of Cirebon culture for future generations by studying the background and motifs of Trusmi batik. This cultural heritage shows how well Indonesia has done in cultivating regional customs that influence textile arts and highlights the diversity and resilience of Indonesian culture, both of which should be respected and preserved.